Sir Small and the dragonfly - O$1 (BConnor, Jane.s; O$1 (BBrien, John,s 1953- (New York : Random House, 1988)
When a dragonfly swoops over the town of Pee Wee and carries Lady Teena away, brave Sir Small rides off on his trusty ant vowing to rescue her.
"Preschool-grade 1"--Cover.
Keywords: Knights and knighthood -- Fiction; Size -- Fiction